2007
DOI: 10.3311/pp.me.2007-2.06
|View full text |Cite
|
Sign up to set email alerts
|

Methods for solving a semi-differential vibration equation

Abstract: Fractional-order (or, shortly, fractional) derivatives are used in viscoelasticity since the late 1980's, and they grow more and more popular nowadays. However, their efficient numerical calculation is nontrivial, because, unlike integer-order derivatives, they require evaluation of history integrals in every time step. Several authors tried to overcome this difficulty. In the followings, some of the proposed methods will be examined for a derivative of order 1 2 (that is sometimes called a semiderivative).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, Schmidt and Gaul [15] have shown that in some cases, this method loses the advantages of fractional calculus over integer-order calculus. Later, this has also been checked by the present author [16] for the field of interest of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, Schmidt and Gaul [15] have shown that in some cases, this method loses the advantages of fractional calculus over integer-order calculus. Later, this has also been checked by the present author [16] for the field of interest of this paper.…”
Section: Introductionmentioning
confidence: 99%